2018
DOI: 10.1186/s13075-017-1508-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel autoantibody against self-vimentin specific in secondary Sjögren’s syndrome

Abstract: BackgroundSjögren’s syndrome (SS) is a primary autoimmune disease (pSS) or secondarily associated with other autoimmune diseases (sSS). The mechanisms underlying immune dysregulation in this syndrome remain unknown, and clinically it is difficult to diagnose owing to a lack of specific biomarkers.MethodsWe extracted immunoglobulins (Igs) from the sera of patients with sSS associated with rheumatoid arthritis (RA) and used them to screen a phage display library of peptides with random sequences.ResultsOur resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition to the usual autoantibodies, a novel reactivity appears to be promising for the differential diagnosis between pSS and sSS. The anti-self-vimentin specific antibody (anti-3S-P) was detected in 68.2% sera from sSS patients (66.2% with sSS-RA and 76.5% with sSS-SLE), and only in 1.8% of pSS, 1.3% of RA, and 4.2% of SLE patients 87…”
Section: Comparison Of Demographic Clinical and Serological Featurementioning
confidence: 99%
“…In addition to the usual autoantibodies, a novel reactivity appears to be promising for the differential diagnosis between pSS and sSS. The anti-self-vimentin specific antibody (anti-3S-P) was detected in 68.2% sera from sSS patients (66.2% with sSS-RA and 76.5% with sSS-SLE), and only in 1.8% of pSS, 1.3% of RA, and 4.2% of SLE patients 87…”
Section: Comparison Of Demographic Clinical and Serological Featurementioning
confidence: 99%
“…Sjögren's syndrome (SS) is a systemic autoimmune disease characterized by marked reduction of exocrine glandular secretions and by its progression to lymphocytic infiltration and destruction [1].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the downregulation of E-cadherin could be balanced by the increased expression of N-cadherin [ 35 , 36 ]. Vimentin, as a typical marker, can regulate a variety of cell types involved in cell migration and enhance cell invasiveness [ 37 , 38 ]. This study showed that PA increased the expression of E-cadherin and decreased the expression of N-cadherin and Vimentin.…”
Section: Discussionmentioning
confidence: 99%